Nonlocal multipoint (in time) problem for evolutionary pseudodifferential equations with analytic symbols in spaces of type $W$ - Horodets’kyi, V. V.; Martynyuk, O. V.; Petryshyn, R. I. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
UDC 517.956 The correct solvability of a nonlocal multipoint (in time) problem for the evolution equations with differentiation operators of infinite order is established for an infinite time interval and an initial function, which is an element of the space of generalized functions of the type $ W'$. The properties of the fundamental solution and the behavior of the solution as $ t → + ∞ $ are investigated.